Sistem Kajian Literatur : Pengaruh Bisnis E-Commerce Terhadap Permintaan Jasa Audit E-Commerce - Adinda Ayu Prameswari; Nur Amalina Widya Pangestika; Siti Fadilla Masitho; Dien Noviany Rahmatika (Jurnal Riset Akuntansi, 2024)
Internet usage has increased rapidly in recent years. Following its development, many companies have become more competitive by cooperating with electronic commerce or e-commerce. The ability to conduct transactions between two or more people using a computer network is called e-commerce. In e-commerce, all transactions are conducted electronically and some accounting systems can be accessed by external parties, thus affecting the internal control of the company. This raises new issues related to business operations, licensing and security of company assets. Since all evidence is electronic, this change also affects the company's audit work carried out by external auditors. External auditors need to understand the internal accounting control system to obtain reliable evidence. External auditors must use audit software to collect evidence, analyze evidence, and test internal and external controls. Therefore, the purpose of this study is to determine whether there is a significant influence between audit information and e-commerce on audit services. This study uses a systematic literature review (SLR) to systematically analyze most articles published between 2019 and 2024.